Graduate Tracking Systems and Employment Outcomes in Nigerian Tertiary Institutions - Niyi Jacob Ogunode (Global Academy of Business Studies, 2026)
Purpose: This paper explores the importance of graduate tracking systems in Nigerian tertiary institutions and examines their implications for improving educational quality, institutional accountability, and workforce development. Specifically, it highlights how graduate databases can help institutions track alumni career outcomes and adapt to labor market demands. Research Methodology: The paper employs a review-based research design, analyzing scholarly works, policy documents, institutional reports, and publications on graduate tracking systems and employment outcomes. Thematic analysis is used to identify key themes such as curriculum development, accreditation processes, and employment trends. Results: The findings emphasize that effective graduate databases are essential for improving curriculum, supporting accreditation efforts, and fostering alumni engagement. These systems also help institutions assess their contribution to national development and improve students' employability. Conclusions: The paper concludes that without structured graduate databases, Nigerian institutions face challenges in aligning educational outputs with labor market needs. Graduate tracking systems are vital for enhancing data-driven decision-making, accountability, and the relevance of education. Limitations: The study is limited by its review-based nature and does not involve primary data collection or empirical research. Contribution: This paper contributes to the ongoing discussion on enhancing higher education practices in Nigeria by advocating for the development of robust graduate tracking systems that improve institutional planning, curriculum effectiveness, and graduate employability.